Framework for forest resource accounting: factoring in the intangibles. (1st June 2008) - Verma, M
Under-valuation of forest resources in India is causing immense losses to the sector and to the economic system. The current national accounting system under-records tangible benefits and ignores the contribution of intangible ecological services by forests. Thus, the values charged for diverting forest land for non-forestry purposes consider only the market value of, for example, timber and some non-timber forest products. The many ecological services also lost in use diversions have never been considered. It is also not really known how to put a value on such services, when a region is reforested. This paper is an attempt to develop a valuation and accounting framework for intangibles from forests, to reflect the true contribution of the forestry sector to the Indian economy. This framework would also help the forestry sector obtain its due share of budgetary allocations and encourage investment in the sustainable management of forests.